Madrasah Readiness in Providing Disabled Friendly Services: : Lesson Learned From 4 Madrasas in Central Java and DI Yogyakarta - Dani, Fatimatuz Zahro Diah Putri; Khoiriyani, Fauziah; Ansyah, Rahmat Husein Andri (PLD UIN Sunan Kalijaga, 2023)
This study aims to investigate how far the readiness of Madrasahs in providing disability-friendly services, what are the obstacles, and how is the government’s disabled-friendly services in madrasahs. This is qualitative research with the case study of 4 madrasahs in Central Java and DI Yogyakarta. Data were collected through observation and in-depth interviews and analyzed using a thematic analysis technique. This research finds several important findings. Firstly, the commitment to disabled-friendly services is already there, however, the quality needs serious improvements such as the lack of standard and user-testing of the facilities so that it can provide appropriate services as intended. Secondly, the biggest obstacle to providing disabled-friendly services is the mindset of institutions. Therefore, a change in the mindset of the institution is needed to provide disable-friendly services aimed at improving long-term and fair services.